Self-management in the process of online education - Марчук, Ірина Петрівна; Марчук, І. П.; Marchuk, Iryna P. (Одеса : Фенікс, 2026)
The subject of the research – the issues of self-management in the educational process in cyberspace. The purpose of the paper is the theoretical analysis of vital space of education and practical approach to its use. This study examines the phenomenon of self-management within the context of online education. The objective is to provide a theoretical exploration of the educational environment in cyberspace and to outline practical approaches to its application. The relevance of this research is underscored by Ukraine’s active integration into the global information space through personal computers and digital networks.
Marchuk, I. P. Self-management in the process of online education. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 567-568. URL: https://doi.org/10.32837/11300.33110
Keywords: самоменеджмент; освіта; онлайн-взаємодія здобувачів освіти; саморегуляція; навчальна залученість у закладах вищої освіти; self-management; education; students’ online interaction; self-regulation; learning engagement in higher education